Volunteer and peer support during the perinatal period: a scoping study - Thomson, G; McLeish, J (Medical Education Solutions, 2018)
We report findings from a scoping study to explore the focus and range of organised volunteer/peer support projects offering support to parents during pregnancy, birth and early childhood in the UK and Republic of Ireland. An online survey was issued to conference attendees and pre-existing contacts, and snowball methods were employed. Twenty-eight valid responses were received. Data identified wide variations in geographical distribution, size and scope, and length of training; many projects relied on multiple sources of funding. While the focus and aims of the projects varied considerably, emotional support was a central tenet in all. A supportive infrastructure was evident in terms of flexible, needs-led support for serviceusers, and training opportunities for volunteers/peer supporters. Three-quarters had an underpinning theory of change or logic model, but there was no consistency in how or what outcomes were measured. Realistinformed research should be undertaken to ‘test’ the theoretical models in practice.